2017
DOI: 10.1037/tps0000100
|View full text |Cite
|
Sign up to set email alerts
|

When (and how) interacting with technology-enhanced storybooks helps dual language learners.

Abstract: In a meta-analysis, Takacs, Swart, and Bus (2015) found that when children listen to multimedia electronic storybooks, comprehension is higher than when listening to a traditional oral reading of the story. However, adding interactive features reduced the benefit, and for at-risk children, the interactive features reduced comprehension to below that when listening to the reading. Here we report a contrasting effect. Namely, a type of interactive feature that we call simulation has a large positive benefit on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Indeed, in the “Moved by Reading” paradigm ( Adams et al, 2018 ; Walker et al, 2017 ), children engage in embodied simulations by first moving computer images through physical actions that reflect the meaning of sentences in a text, and later creating internal simulations of the text via imagery. Upon doing so, children exhibit significantly better comprehension than controls ( Adams et al, 2018 ), as long as they are good at word decoding ( Walker et al, 2017 ). In line with these antecedents, our research indicates that earliness of language exposure and attained proficiency also represent subject-level variables modulating embodied effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the “Moved by Reading” paradigm ( Adams et al, 2018 ; Walker et al, 2017 ), children engage in embodied simulations by first moving computer images through physical actions that reflect the meaning of sentences in a text, and later creating internal simulations of the text via imagery. Upon doing so, children exhibit significantly better comprehension than controls ( Adams et al, 2018 ), as long as they are good at word decoding ( Walker et al, 2017 ). In line with these antecedents, our research indicates that earliness of language exposure and attained proficiency also represent subject-level variables modulating embodied effects.…”
Section: Discussionmentioning
confidence: 99%
“…Now, except for a few works that have explored comprehension of naturalistic narratives in bilinguals within the simulation theory framework ( Adams et al, 2018 ; Walker et al, 2017 ), this empirical corpus is marked by a major shortcoming: its virtually null ecological validity. Indeed, while the above studies involved randomized series of disconnected and (pseudo)randomized items (for a review, see Kogan et al, 2020 ), daily language processing is based on context-rich texts characterized by cohesion, coherence, and unfolding semantic relations ( Halliday and Matthiessen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of interactive features for children's language outcomes hold not only for children's first language but also if they are learning a second language. Walker, Adams, Restrepo, Fialko and Glenberg (2017) examined how children who were not native English speakers performed on different tasks of reading comprehension when the digital books they read contained additional support in Spanish. They found that adding some interactive support in children's native language improved these children's performance, since it supported their understanding of the story meaning.…”
Section: Considering the Influence Of Interactive Features In Childrementioning
confidence: 99%
“…With the embedded interactive features, digital literacy environments allow for collecting information from the readers and provide options of content and individualized support (McEneaney, 2006). In return, readers can actively choose their preferred content (Bryan et al, 2003), monitor their comprehension (Boteanu et al, 2016), or seek help when necessary (Walker et al, 2017). To this end, this study aims to explore the potentiality of using interactive e-books, as a practice of stealth assessment to track students' reading processes and predict word knowledge and strategic reading outcomes.…”
mentioning
confidence: 99%